Phytochemical Analysis Of Seeds, Stem Bark And Root Of An Endangered Medicinal Forest Tree Oroxylum Indicum(L)Kurz - TALARI SAMATHA; PENCHALA SRINIVAS; RUDROJU SHYAMSUNDARACHARY; MARKA RAJINIKANTH; NANNA RAMA SWAMY (International Journal of Pharma and Bio Sciences, 2012)
The species of Oroxylum indicum is an endangered forest tree known to possess flavonoids, alkaloids, saponins and tannins with significant biological activity. To screen the various medicinally important secondary metabolites and for the identification of the presence of biologically active compounds, standard procedures as described by Brindha et al., (1977), Trease and Evans (1989), Sofowora (1993) and Harborne (1998) were followed. The presence of flavonoids, alkaloids, tannins, sterols, saponins, glycosides, phenols and quinones have been detected. The results of the phytochemical screening of crude extracts from seeds, stem bark and root of Oroxylum indicum showed the presence of bioactive substances that can be used in prevention of major diseases.